Hygienic assessment of the occurrence and development of emotional burnout syndrome among medical students and its prevention - Chorna, Valentyna; Syrota, Hanna; Syrota, Mariia; Khliestova, Svitlana; Poliarush, Vlada; Hudzevych, Lyudmyla (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Emotional burnout syndrome has become increasingly common in recent decades, regardless of the field of professional activity. The purpose of our study was to compare the prevalence of emotional burnout in medical students of Vinnytsia National Medical University before the beginning of the academic semester and during the passing of exams. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. An anonymous, voluntary survey before the start of study was taken by 300 students, among them 82.3% were women, 17.7% were men. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. During the exams, 362 students took part, including 76.2% women and 24.1% men. According to the results of the study, the proportion of the "average" degree of exhaustion increased in second-year students by 15.6%; third-year students by 44.4%. The "high" degree of emotional exhaustion according to the results of the study before the start of training was found in male students of the third year ‒ 44.4% and 36.4% of male students of the sixth year. During the exams, the rate of "high" emotional exhaustion was observed in first-year students, increasing from 12.5% to 18% and in sixth-year students from 36.4% to 50%. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Thus, it was found that female students are the most adapted to the educational load, to passing exams, which affects the psychosomatic state of future doctors.